Assessment of Chlamydia suis Infection in Pig Farmers. Issue 3 (18th November 2015) - De Puysseleyr, L.; De Puysseleyr, K.; Braeckman, L.; Morré, S. A.; Cox, E.; Vanrompay, D.
Summary: Chlamydia suis infections are endemic in domestic pigs in Europe and can lead to conjunctivitis, pneumonia, enteritis and reproductive failure. Currently, the knowledge on the zoonotic potential of C. suis is limited. Moreover, the last decades, porcine tetracycline resistant C. suis strains have been isolated, which interfere with treatment of chlamydial infections. In this study, the presence of C. suis was examined on nine Belgian pig farms, using Chlamydia culture and a C. suis specific real‐time PCR in both pigs and farmers. In addition to diagnosis for C. suis, the farmers' samples were examined using a Chlamydia trachomatis PCR. Additionally, the Chlamydia isolates were tested for the presence of the tet(C) resistance gene. C . DNA was demonstrated in pigs on all farms, and eight of nine farmers were positive in at least one anatomical site. None of the farmers tested positive for C. trachomatis. Chlamydia suis isolates were obtained from pigs of eight farms. Nine porcine C. suis isolates possessing a tet(C) gene were retrieved, originating from three farms. Moreover, C. suis isolates were identified in three human samples, including one pharyngeal and two rectal samples. These findings suggest further research on the zoonotic transfer of C. suis from pigs to humans is needed.